2018
DOI: 10.1111/ijfs.13883
|View full text |Cite
|
Sign up to set email alerts
|

Syrah grape skin valorisation using ultrasound‐assisted extraction: Phenolic compounds recovery, antioxidant capacity and phenolic profile

Abstract: Summary The influence of ultrasound power (1000–3000 W/L), citric acid concentration (0–3%) and solid:liquid ratio (1:5–1:15) on the phenolic compounds recovery and antioxidant capacity of Syrah grape skin extracts were evaluated. Total phenolic compounds varied from 6485 to 11732 mg gallic acid/100 g and monomeric anthocyanin content from 453 to 685 mg malvidin‐3‐glucoside/100 g. The antioxidant capacity measured by ORAC and ABTS methods ranged from 230 to 516 μmol Trolox/g and from 442 to 939 μmol Trolox/g, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Figure 2 E describes the anthocyanin yields dramatically increased when the solid-to-liquid ratio was in the range of 1:10–1:20 g/mL ( p < 0.05). The reason for this phenomenon was that the solid-liquid contact area and concentration gradient increased with the increase of the amount of extraction solvent, which was conducive to the diffusion of anthocyanins from inside the extraction solvent, resulting in improving anthocyanin yields [ 42 ]. Similar results were reported in the case of anthocyanins from blueberry wine pomace by using ultrasonic-assisted extraction [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 E describes the anthocyanin yields dramatically increased when the solid-to-liquid ratio was in the range of 1:10–1:20 g/mL ( p < 0.05). The reason for this phenomenon was that the solid-liquid contact area and concentration gradient increased with the increase of the amount of extraction solvent, which was conducive to the diffusion of anthocyanins from inside the extraction solvent, resulting in improving anthocyanin yields [ 42 ]. Similar results were reported in the case of anthocyanins from blueberry wine pomace by using ultrasonic-assisted extraction [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be due to the low content of these compounds in the peach palm by‐product, and so, their content in the extracts analyzed did not reach the limit of detection by HPLC analysis. Moreover, these phenolics were not detected in other studies (Kazemi, Karim, Mirhosseini, & Hamid, 2016; Mazza et al, 2018; Wang et al., 2019).…”
Section: Resultsmentioning
confidence: 68%
“…Mazza et al. (2019) determined 6,485 to 11,732 mg gallic acid/100 g total phenolic contents and they reported that the antioxidant capacity measured by ORAC and ABTS methods ranged from 230 to 516 µmol Trolox/g and from 442 to 939 µmol Trolox/g in Syrah grape skin extracts, respectively. Antioxidant activity values of vine leaf extracts collected in May and September were determined as 61.69 and 70.32, respectively (Katalinic et al., 2009).…”
Section: Resultsmentioning
confidence: 99%